A matriz paranóica do amor em O príncipe com orelhas de burro de José Régio - Ferreira, Nadiá Paulo (2011)
The reading of O príncipe com orelhas de burro (The prince with donkey ears), by José Régio is designed mainly to highlight the following issues: the aesthetic obligations of Presença movement, the use of allegory in the sense of Walter Benjamin and the structure of paranoid hero.